The Effect of a Nutrition Education Program on Improving Hemoglobin A1c and Body Mass Index of Patients with Type 2 Diabetes Mellitus in Erbil City: A Non-randomized Clinical Trial - Hawraz F. Saadi; Wali O. Omer (Polytechnic)
mellitus (DM) among individuals of all age ranges in both developed and developing countries. Changing the patients’ lifestyles by modifying their diet through nutrition education programs decreases their body mass index (BMI), hemoglobin A1c (HbA1c), and reverses DM. This study aimed to determine the effect of a proposed nutrition education program on BMI and HbA1c among patients with type 2 DM (T2DM). The present clinical trial was conducted on 42 patients with T2DM in Diabetes Center in Erbil-Kurdistan Region-Iraq, from December 2018 to September 2019. Data were collected using a customs questionnaire before the study and after educational sessions in which the patients were educated about an appropriate diet based on a proposed nutrition education program. In the first session and after third session, the patients’ BMI and HbA1c were measured. According to the results, most of the patients aged 45–64 years, a majority of the patients lived in urban areas (95.2%), were illiterate (33.3%), and were obese (76.2%). Due to the nutrition education program, remarkable decrease was observed in the patients’ high (BMI) and high HbA1c and experienced a mean decrease of (2.6%) from 34.0 ± 5.6 to 31.4 ± 5.2, and HbA1c decreased about (2.0%) on average from 8.9 ± 1.9 to 6.9 ± 0.9. High BMI and high HbA1c can be controlled and decreased through appropriate nutrition education programs.